FORENSIC CHARACTERISTICS OF SPINAL CORD INJURIES IN PEDESTRIANS INJURED IN COLLISIONS WITH VEHICLES (World Bulletin of Public Health, 2024)
Spinal cord and spinal cord injuries in the structure of injuries of the musculoskeletal system account for up to 17.8%, after which, with complicated spinal cord lesions, persistent disability develops in 80.0-95.0% of patients. The forensic aspects of spinal cord injuries have not been systematized to date. In order to identify the mechanism of formation and morphological features of damage to the structures of the spine and spinal cord in pedestrians injured in an accident, the results of forensic examinations were analyzed in relation to 215 corpses of adults, as well as the corpses of 140 children who died in collisions with moving cars. It has been established that the formation of cervical-occipital trauma in adult pedestrians injured in an accident is associated with phase 1, and the nature of damage to the structure of the cervical and upper thoracic spine, having a rotational distraction character with traumatization of their posterior processes and often the separation of the spine at the level of fractures, indicate their occurrence in the 1st and the 2nd phases of car injury. In pedestrian children injured in an accident, in the structure of spinal cord injury, injuries to the upper and lower middle vertebrae (distraction and rotation) are often observed, which sometimes occur with the separation of the spinal column and spinal cord in the fracture area. These data indicate that damage to these structures occurs in the 1st phase (injury of the thoracolumbar spine) and in the 2nd phase (injury of the cervical spine) of an automobile injury.
Keywords: traumatization; structures; phase; column